Crime, material and meaning in art world desirescapes: how matter matters for art crime - Yates, Donna (Crime and art, 2021)
In this chapter we propose the idea of a ‘desirescape’, where a spatial array of myriad agentic objects cultivates desire among people to collect, own, possess, and show off artworks. Within this desirescape, people are conceived of as caught in a web of objects that not only generate and manipulate desire, but also disturb reason. Moving away from a human-oriented sociology of art worlds, we explore the object networks of art within market spaces (dealerships, museums, art fairs, auctions) to consider how actor-objects active create a network into which human-subjects are drawn. We then consider how these object-networks might lead to the violation of ethical or social norms or the committing of a crime. While we ultimately advocate for an expansion of object-focused criminological theory, this work has immediate practical implications. Criminologists may benefit from thinking about crime prevention priorities in terms of changing the network properties of these webs of alluring objects, rather than focussing on the more traditional technique of dissuading individuals from committing crime through responding to these allures.